Freedom from violence and lies : Anton Chekhov's life and writings - Finke, Michael C., 1957- (Reaktion Books, 2021)
An enlightening, nuanced, and accessible introduction to the life and work of one of the greatest writers of short fiction in history.Anton Chekhov's stories and plays endure, far beyond the Russian context, as outstanding modern literary models. In a brief, remarkable life, Chekhov rose from lower-class, provincial roots to become a physician, leading writer, and philanthropist, all in the face of a progressive fatal disease. In this new biography, Michael C. Finke analyzes Chekhov's major stories, plays, and nonfiction in the context of his life, both fleshing out the key features of Chekhov's poetics of prose and drama and revealing key continuities across genres, as well as between his lesser-studied early writings and the later works. An excellent resource for readers new to Chekhov, this book also presents much original scholarship and is an accessible, comprehensive overview of one of the greatest modern dramatists and writers of short fiction in history.